2012
DOI: 10.1016/j.ymeth.2012.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Protein microarrays, biosensors, and cell-based methods for secretome-wide extracellular protein–protein interaction mapping

Abstract: Approximately one quarter of all human genes encode proteins that function in the extracellular space or serve to bridge the extracellular and intracellular environments. Physical associations between these secretome proteins serve to regulate a wide range of biological activities and consequently represent important therapeutic targets. Moreover, some extracellular proteins are targeted by pathogens to allow host access or immune evasion. Despite the importance of extracellular protein-protein interactions, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 98 publications
(115 reference statements)
0
18
0
Order By: Relevance
“…To help our understanding of axon guidance, the full complement of extracellular signaling molecules must be uncovered. The application of technologies for screening extracellular protein-protein interactions is an emerging approach for identifying unknown axon-guidance molecules [38]. In one example, a screening methodology called AVEXIS was used to interrogate the interactions among 150 zebrafish receptors from the leucine-rich-repeat and/or Ig superfamily expressed in the nervous system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To help our understanding of axon guidance, the full complement of extracellular signaling molecules must be uncovered. The application of technologies for screening extracellular protein-protein interactions is an emerging approach for identifying unknown axon-guidance molecules [38]. In one example, a screening methodology called AVEXIS was used to interrogate the interactions among 150 zebrafish receptors from the leucine-rich-repeat and/or Ig superfamily expressed in the nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Here we have utilized an extracellular protein microarray that allows efficient screening of nearly one-third of the known human secreted or cell-surface expressed, single-transmembrane-containing genes [24], [38]. Prior work has shown that the microarray approach is able to robustly identify the majority of expected interactions within the Ig receptor family, including those having low binding affinities [24], [39].…”
Section: Discussionmentioning
confidence: 99%
“…Protein microarrays offer the unique advantage of requiring minimal consumption of protein reagents, fast readouts, and relatively more affordable instrumentation. Typically, a fluorescently labeled or tagged protein of interest (the bait) is generated as a recombinant product and screened against all proteins in the array [10,53]. Despite the increased availability of highcoverage protein arrays, very few are focused on extracellular proteins and therefore are not suitable for study of hostpathogen ePPIs.…”
Section: Protein Microarraysmentioning
confidence: 99%
“…The protein microarrays have represented one of the most fruitful approaches for unbiased determination of ePPIs, including host-pathogen interactions. Nevertheless, one of the main limitations of this technology is the need to generate comprehensive libraries, a process that is resource consuming and often not available to many researchers [53,93]. Consequently, although some of the available arrays were designed to cover a significant fraction of the human proteome, any discoveries made using these platforms are limited to the proteins present in each array.…”
Section: In Vitro Transcription and Translation-(ivtt-) Basedmentioning
confidence: 99%
See 1 more Smart Citation